(untitled) (American Journal of Arts and Human Science, 2024)
To maintain overall health and well-being, one must practice good sleep hygiene. However, the literature has not sufficiently addressed the relationship between Sleep Hygiene and Mood States. This study evaluated the association between Sleep Hygiene Practices and Mood States, including the influencing factors. This study utilized a descriptive-predictive research design on 350 college students in the chosen University in Davao Region through simple random sampling. The researchers used the Shapiro-Wilk Test, which indicates normally distributed data with a p <0.05. The study analyzed the relationship between Sleep Hygiene and Mood States using Pearson’s Correlation Coefficient, revealing a significant positive correlation coefficient of r =.439 and a p of <.001, suggesting that if the Sleep Hygiene practices of students are high, the Mood States is also high. Furthermore, linear regression revealed that bedroom factors and behaviors that affect sleep are the predictors that contribute to the students’ mood states. The study recommends implementing policies to promote a healthy campus environment, prioritizing healthy sleep habits for students and teachers, and for future researchers to advocate for broader, longitudinal studies to enhance understanding and validity.